2020
DOI: 10.3847/1538-4357/ab9363
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Anoxic Abiotic Habitable Planet Atmospheres: Impact of New H2O Cross Sections

Abstract: We present a study of the photochemistry of abiotic habitable planets with anoxic CO 2-N 2 atmospheres. Such worlds are representative of early Earth, Mars, and Venus and analogous exoplanets. Photodissociation of H 2 O controls the atmospheric photochemistry of these worlds through production of reactive OH, which dominates the removal of atmospheric trace gases. The near-UV (NUV; >200 nm) absorption cross sections of H 2 O play an outsized role in OH production; these cross sections were heretofore unmeasure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 104 publications
1
78
0
Order By: Relevance
“…The new VUV section will provide temperature-dependent absorption cross sections. Recent results suggest the VUV absorption by H 2 O enhances the production of OH, which plays an important role in the atmospheric chemistry of exoplanetary atmospheres [254] . Currently, the VUV cross sections are provided for H 2 O, H 2 , CO 2 , SO 2 , NH 3 , H 2 CO and C 2 H 4 measured by Fateev's lab at the Danish Technical University (DTU) [255] and for CO 2 by Venot et al [256] .…”
Section: Vuv Sectionsmentioning
confidence: 99%
“…The new VUV section will provide temperature-dependent absorption cross sections. Recent results suggest the VUV absorption by H 2 O enhances the production of OH, which plays an important role in the atmospheric chemistry of exoplanetary atmospheres [254] . Currently, the VUV cross sections are provided for H 2 O, H 2 , CO 2 , SO 2 , NH 3 , H 2 CO and C 2 H 4 measured by Fateev's lab at the Danish Technical University (DTU) [255] and for CO 2 by Venot et al [256] .…”
Section: Vuv Sectionsmentioning
confidence: 99%
“…In the current paper, we additionally introduced some minor updates compared to the photochemical model described in Wunderlich et al (2020). Recently, the water (H 2 O) cross section between 186-230 nm has been measured by Ranjan et al (2020) for a temperature of 292 K. We use this new cross section data in the current study. However, the weak NUV flux of M dwarfs suggests that the water photolysis is not affected significantly by the usage of the new measurements (see e.g.…”
Section: Model Description and Updatesmentioning
confidence: 99%
“…For this work, we assume a 0.3 bar atmosphere composed of 33% N 2 , 33% CO, and 33% CO 2 with water at vapor pressure, the same as the >3.5 Ga atmosphere Rimmer et al ( 2019 ) used to explain the observed micrometeorite oxidation from the work of Tomkins et al ( 2016 ), and consistent with other early Earth model atmospheres invoked to explain the same data (Lehmer et al , 2020 ; Payne et al , 2020 ). We solve for the surface UV flux using the model of Rimmer & Helling ( 2016 ) and Rimmer and Rugheimer ( 2019 ) with the UV absorption and scattering cross sections from PHIDRATES (Huebner et al , 1992 ; Huebner and Mukherjee, 2015 ) for most species, with updated cross sections for CO 2 (Ityaksov et al , 2008 ), HCHO (Chen and Zhu, 2001 ), H 2 O (Ranjan et al , 2020 ), and CH 4 (Burkholder et al , 2020 ). Most of these cross sections were obtained from the Mainz database (Keller-Rudek et al , 2013 ).…”
Section: Simulating the Young Sunmentioning
confidence: 99%